FROM NOTHING TO SOMETHING - Genoveva Genoveva; Amira Nurul Azmi; Eggy Asyrofi (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTAn orphanage is a place to accommodate children who do not have parents or guardians sothat they get proper education and facilities. The problem faced by community-run orphanages issustainability. The GIA Foundation is a social foundation established by the community in theJababeka industrial area to accommodate orphans or children whose parents cannot afford theirchildren's education. To help the sustainability of the orphanage, the auhtors are students andsupervisor who are currently carrying out a CSR project as part of the Entrepreneurship course. Weprovide entrepreneurship training, theoretical as well as handicraft making skills. With theknowledge and skills they have, it is hoped that the residents of the orphanage can be empoweredto become economically independent, namely by selling handicrafts from used materials to becomevaluable handicrafts. This activity still needs continuation so that the skills of the orphanage childrenare better and the results are marketable.Keywords: Social project, corporate entrepreneurship, orphanage